Pelatihan Instruksi Berbasis Multimodal Untuk Pengajaran Jarak Jauh Guru MGMP Bahasa Inggris SMA Provinsi Kalimantan Selatan - Noor Aida Aflahah; Al Farhan, Miftah; Yansyah Yansyah; Hafizhatu Nadia; Tenny Murtiningsih (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2024)
Over time, learning limitations become increasingly visible during the COVID-19 outbreak with indicators such as students starting to become less enthusiastic about learning, feeling a lack of interaction, and various technical problems such as internet network fluctuations. Some of these problems lead to a decrease in the quality of learning. This community service aims to provide assistance to MGMP English High School teachers in South Kalimantan regarding the implementation of multimodal-based instruction. There were 28 teachers who attended the event. The methods used were lectures, simulations and discussions via Zoom and assignments on Open Learning. The result of this community service is that teachers gain inspiration in online learning and can increase student motivation. The problem faced by teachers is that teachers need a lot of time to prepare material and an unstable internet connection.